Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Kasus Pada Rocket Chicken Cabang Jombang Satu) - Egi Fauzi Suhaerul Bustami (BIMA : Journal of Business and Innovation Management, 2019)
The development of the world economy is increasingly consumer behavior change resulted in forward in terms of the fulfillment of his needs, this company must continue to innovate in creating strategy of price and quality of service interesting in order to maintain its existence. Customer satisfaction is one of the keys to the success of the company is very noteworthy. This research aims to know the influence of the price and quality of service of consumer satisfaction in the Rocket Chicken Branch Stubs. Research methods used in this research is quantitative research methods and the type of survey research (research survey) with the data analysis techniques using multiple linear regression techniques. the population in this research is the entire consumer Rocket Chicken Branch Stubs one by the number of samples taken as many as 100 respondents. Research results showed partially prices and service quality to customer satisfaction, while simultaneously the price and quality of services to the satisfaction of the consumer. should party Rocket Chicken Branch stubs pay attention to pricing and quality of service in order to increase customer satisfaction.